What clinicians and patients want: The past, the presence, and the future of the botulinum toxins. (15th April 2020) - Kivi, Anatol; Ri, Songjin; Wissel, Jörg
Abstract: Botulinum toxin (BoNT) is well established in clinical practice for more than 30 years. During this time the area of applications was broaden beyond the ophtalmologic and neurologic indications. Despite of decades of BoNT application with a huge increase of expertise and supporting methods for utilization as well, both patients and physicians claim about boundaries and limits in their daily treatment practice. Most of those limits are related to the toxin itself and its pharmacokinetic properties. The challenge in the field of movement disorders, swetting, and sialorrhea to combine all fast onset, long-lasting effect, safe application free of pain, and the possibility to vary therapy strategies in dosage and application intervals is pervasive and recurrent. In the present article we attempt to name challenges, patient's and physician's wishes. On the base of the toxins that we have and that we are going to get we imagine optimized therapy settings for the core neurological indications spastic movement disorder, dystonia, swetting, and sialorrhea. Highlights: Paradigm shift in BoNT research. Toxin engineering. Individualized medicine.